A fast inverse dynamics model of walking for use in optimisation studies. Issue 11 (17th August 2016) - Salehi, Hadi; Ren, Lei; Howard, David
Abstract: Computer simulation of human gait, based on measured motion data, is a well-established technique in biomechanics. However, optimisation studies requiring many iterative gait cycle simulations have not yet found widespread application because of their high computational cost. Therefore, a computationally efficient inverse dynamics model of 3D human gait has been designed and compared with an equivalent model, created using a commercial multi-body dynamics package. The fast inverse dynamics model described in this paper led to an eight fold increase in execution speed. Sufficient detail is provided to allow readers to implement the model themselves.